KOCH, INGEDORE GRUNFELD VILLAÇA (2002). Desvendando os segredos do texto. São Paulo: Cortez. 188 pp. ISBN 85-249-0837-8 (Revista Latinoamericana de Estudios del Discurso, 2021)
KOCH, INGEDORE GRUNFELD VILLAÇA (2002). Desvendando os segredos do texto. São Paulo: Cortez. 188 pp. ISBN 85-249-0837-8.